Wissenskulturen im Dialog Experimentalräume zwischen Wissenschaft und Kunst - Ingrisch, Doris 1957-; Mangelsdorf, Marion; Dressel, Gert 1964- (transcript, 2017)
Encounters between different cultures of knowledge can be unsettling for both parties. Everything that in one academic or artistic discipline is considered secure knowledge loses its self-evidence in the face of both inter-, trans-, and post-disciplinary
Keywords: Artistic Research; Kultur; Kulturtheorie; Kulturwissenschaft; Kunst; Kunstbasierte Forschung; Kunstwissenschaft; Postdisziplinarität; Transdisciplinarity,Postdisciplinarity,Science,Art Based Research,Artistic Research,Knowledge,Art,Culture,Cultural Theory,Sociology of Science,Fine Arts,Cultural Studies; Transdisziplinarität; Wissen; Wissenschaft; Wissenschaftssoziologie; Culture; Künstlerische Forschung; Interdisziplinarität; Künste; Aufsatzsammlung